THE AUTHORITY OF LOCAL GOVERNMENTS IN PREVENTING AND ERADICATION OF FOREST DESTRUCTION - Hidayat, Fatah; Utama, Cholidah (Nurani, 2021)
Forest damage in Indonesia has been increasing from year to year, both forest damage caused by illegal logging, forest burning, mining without permits, and plantations without permits have caused state losses, damage to socio-cultural life and the environment, as well as increasing global warming which has become national, regional and international issues. Forest damage caused by forest fires carried out by the community both for clearing agricultural land and for plantation land, burning forests and land seems to never stop threatening the lives of people in Indonesia because most Indonesian people become farmers, especially those in the regions. who must clear forests for agricultural land. This is because local governments have the authority to regulate and limit the permits of companies operating in the forestry, plantation and mining sectors in their respective areas. Therefore, local governments must make policies and make concrete mitigation in terms of preventing and eradicating forest destruction that occurs in each region.